Antioxidant and cardioprotective activity of Stachys schimperi Vatke against doxorubicin-induced cardiotoxicity - Essam Abdel-Sattar; Sabah Hussein El-Gayed; Ibrahim Shehata; Osama M. Ashour; Ayman A. Nagy; Ahmed M. Mohamadin (Faculty of Pharmacy, Cairo University, 2012)
Cardiotoxicity is one of the major side effects of anthracycline antibiotics. Most studies implicated increased oxidative stress as the major determinant of doxorubicin (DOX) cardiotoxicity. The aim of the current investigation was to study the possible cardioprotective effect of Stachys schimperi Vatke (family Lamiaceae) on DOX-induced cardiotoxicity in rats based on biochemical and histopathological parameters. The phenolic profile of the methanol extract was determined qualitatively by HPLC. Isoscutellarein 7-O-[2"-O-(6"'-acetyl)-β-d-allopyranosyl]-β-d-glucopyranoside (compound 1) was isolated and identified from EB fraction as a major constituent for the first time from this Stachys species. The methanolic extract and the combined EtOAc and n-butanol fractions (EB) as well as compound 1 showed prominent free radical scavenging activity when assessed by the DPPH method. The methanolic extract showed moderate protection against DOX-induced alteration in cardiac oxidative stress markers; GSH and MDA, and cardiac serum markers; CK-MB and LDH activities. Additionally, histopathological study denoted mild protection against DOX-induced cardiotoxicity. It was concluded that Stachys schimperi Vatke methanolic extract protected against DOX-induced cardiotoxicity, at least in part, by virtue of its antioxidant activity.